KRUSKAL WALLIS ANALYSIS TO FIND OUT THE IMPROVEMENT OF DESIGN THINKING SKILLS IN OBJECT-ORIENTED PROGRAMMING MATERIALS THROUGH EDUCATIONAL CONTENT - Eka Fitrajaya Rahman; Hanum Salsabilla; Harsa Wara Prabawa (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Education legislation in Indonesia currently requires Informatics subjects, which is closely related to programming-based material. However, many students in Indonesia still have difficulty learning about programming material. One of them is due to the background of students about the ability to think in the process of solving a program code. Seeing the phenomenon of today's students who are active on social media, it is a good step if social media is used as a learning media platform. This study aims to analyze the improvement of design thinking skills by using educational content-based learning media. The research method used was R&D with the ADDIE media development model and One Group Pretest-Posttest as the research design. The results showed an increase after students were given treatment in the form of educational content based learning media. The Kruskal Wallis test results showed a significant difference between the upper class, middle class, and lower class. The N-Gain obtained in the upper class is 0.560, in the middle class is 0.505, and in the lower class is 0.303. The average value of the results of student responses to learning media is 96.59 percent with the category